Two new species and two new records of Ptecticus Loew (Diptera: Stratiomyidae: Sargiinae) from China - Yang, Zai-Hua; Chen, Xiao-Ming; Yang, Mao-Fa (Zootaxa, 2015)
Two species, Ptecticus brevispinus sp. nov. and P. guangxiensis sp. nov., from China are described and illustrated. Additional two species, P. longispinus Rozkošný & Kovac, 2003 and P. melanurus (Walker, 1848), are recorded from China for the first time. A checklist of the known Chinese Ptecticus Loew, 1855 species together with their geographical distribution and a new identification key (19 spp.) are presented.